A ficção legal trazida pelo parágrafo primeiro do artigo 54 da Lei n. 13.097/2015 enquanto princípio positivo da fé pública registral e seus efeitos substantivos - Romiti, Angela Patrício Müller (2025)
This thesis the aim is to, materially analyze, the first paragraph, of article 54, of Law 13.097/2015 as a positive principle of public registration faith – foundation, legal nature, legal preconditions, requirements and, effects as a solutio to the unwanted qualified registration inaccuracy pathology and its consequences in the face of the third-party acquirer under registration faith. The investigation was summarized in the quaestio: Does the incidence of the positive principle of the public registration faith require a departure from the general principals of nemo plus iuris, resoluto jure concedenti, resolvitur jus accipiens, nemo dat quod non habet, quod nullum est nullum producit effectum? Is it a kind of appearance’s guardianship? It is excluded from its object, thus, the negative aspect of public registration faith derived from the presumption of the registration completeness – and, also known as the principle of unenforceability – and implications regarding adjective law. This present study is justified whereas, despite the ten years of validity of Law 13.097/2015, its systematic impact is ignored by the Courts and, disregarded by the national doctrine that, satisfied with the statement – sic et simpliciter – that the device enshrines, in Terra Brasilis, the principle of public registration faith with migration of the national system to the so-called strong protection systems. The conclusion, not rarely, is based on foreign doctrine, forgetting, however, that the Brazilian tabular system is unique (tertium genus), and there is no similar system in other countries, so that the legal-scientific production of other adopting countries of the guardianship regime of the third mortgagee, whether Germany, Portugal, Italy, Spain, Switzerland or Austria, even if they maintain some aspects of proximity, proves to be mistaken. In this line of reasoning, with the purpose of eradicating false premises, it was opted for the inductive method and, based on the normative hypothesis of the first paragraph of article 54, of Law 13.097/2015, as a positive principle of public registration faith, achieved the conclusions induced from propositional-abstractions. However, in an attempt to make a simple contribution, this thesis proves to be unprecedent due to its method, verticalization, extension and result. At last, without intending to boast an analytical statement, another perspective is presented on the positive principle of public registration faith, as a form of original acquisition of property, legitimizing the registration position of the third mortgagee, which, based on registration security. Protected because it is an evident right – not protection of appearance – it extracts from the material effects derived from the registration a new substantive reality, rights creator